Medication Adherence and Perceptions According to the Presence or Absence of a Migration Background in a Dialysis Unit (DIANA Qualitative Study) - Dotta-Celio J; Lelubre M; Bolzon S; Halabi G; Burnier M; Bodenmann P; Pruijm M; Schneider MP (Patient Preference and Adherence)
Jennifer Dotta-Celio,1– 3 Mélanie Lelubre,1– 3 Sabrina Bolzon,1– 3 Georges Halabi,4 Michel Burnier,5 Patrick Bodenmann,6,7 Menno Pruijm,4,* Marie P Schneider2,3,* 1Department of Ambulatory Care, Pharmacy, Unisanté, Center for Primary Care and Public Health & University of Lausanne, Lausanne, Switzerland; 2School of Pharmaceutical Sciences, University of Geneva, Geneva, Switzerland; 3Institute of Pharmaceutical Sciences of Western Switzerland, University of Geneva, University of Lausanne, Geneva, Switzerland; 4Service of Nephrology and Hypertension, Department of Medicine, Lausanne University Hospital and University of Lausanne, Lausanne, Switzerland; 5Faculty of Biology and Medecine, University of Lausanne, Lausanne, Switzerland; 6Department of Vulnerabilities and Social Medicine, Unisanté, Center for Primary Care and Public Health & University of Lausanne, Lausanne, Switzerland; 7Chair of medicine for Vulnerable Populations, Faculty of Biology and Medicine, University of Lausanne, Lausanne, Switzerland*These authors contributed equally to this workCorrespondence: Marie P Schneider, Institute of Pharmaceutical Sciences of Western Switzerland (Institut Des Sciences Pharmaceutiques de Suisse Occidentale - ISPSO) 1 Rue Michel-Servet, Genève, 1211, Switzerland, Tel +41.22.379.36.18, Email marie.schneider@unige.chPurpose: Migration status has received little attention in the context of medication adherence. This qualitative study aims to consolidate the findings of the quantitative DIANA study by: 1) exploring medication management, medication knowledge and perceptions and 2) identifying whether there are differences in medication management, knowledge and perceptions between patients according to the patients’ migration status.Patients and Methods: This monocentric qualitative study was part of the research protocol DIANA (Dialyse chronique et adhésion thérapeutique). Patients were recruited at the chronic dialysis unit of the Lausanne University Hospital. In-depth, face-to-face interviews were conducted; for allophone patients, an interpreter was present. Each interview was recorded and transcribed verbatim. A content analysis was performed.Results: Eighteen interviews were performed. Nine patients were Swiss, 3 had a residence/settlement permit, 6 were provisionally admitted/asylum seekers. Six interviews were performed with an interpreter. Core themes were: (1) treatment management (medication intake had become a habit, forgetting was rare), (2) heterogeneous treatment knowledge but highly perceived necessity, (3) reported medication disadvantages were pill burden and side effects, (4) role of the patient in the medical environment (trust in physicians but patients making decisions regarding their treatment on their own, without consulting healthcare professionals). Swiss patients engaged more in shared decision-making and were more likely to talk about side effects than migrant patients. Provisionally admitted foreign nationals/asylum seekers talked more about their gratitude to the healthcare system.Conclusion: More studies are needed to understand how shared decision-making can be established between health professionals and patients, taking into account their migration status. To provide tailored education, it is essential to evaluate patients’ health literacy and to use the teach-back method to find the best way to convey health messages. The acquisition of transcultural clinical skills by health professionals is necessary to support medication adherence.Keywords: patient adherence, renal dialysis, polypharmacy, culture, migrants